2003
DOI: 10.1128/jvi.77.10.5948-5963.2003
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus σNS and μNS Proteins Form Cytoplasmic Inclusion Structures in the Absence of Viral Infection

Abstract: Reovirus replication occurs in the cytoplasm of infected cells and culminates in the formation of crystalline arrays of progeny virions within viral inclusions. Two viral nonstructural proteins, NS and NS, and structural protein 3 form protein-RNA complexes early in reovirus infection. To better understand the minimal requirements of viral inclusion formation, we expressed NS, NS, and 3 alone and in combination in the absence of viral infection. In contrast to its concentration in inclusion structures during r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
123
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 103 publications
(130 reference statements)
3
123
0
Order By: Relevance
“…The inclusions formed by NS in such experiments are notably similar in appearance to globular reovirus factories formed in infected cells, as visualized by either phase-contrast or immunofluorescence (IF) microscopy (4,7,30), suggesting that NS forms the matrix of the factories (7). Moreover, NS can associate with several other reovirus proteins and recruit them to these inclusions in transfected cells.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…The inclusions formed by NS in such experiments are notably similar in appearance to globular reovirus factories formed in infected cells, as visualized by either phase-contrast or immunofluorescence (IF) microscopy (4,7,30), suggesting that NS forms the matrix of the factories (7). Moreover, NS can associate with several other reovirus proteins and recruit them to these inclusions in transfected cells.…”
mentioning
confidence: 73%
“…Results from our laboratory and others have recently shown that a single reovirus protein, NS, is sufficient for forming phase-dense globular inclusions in the cytoplasm of transfected cells (4,7). The inclusions formed by NS in such experiments are notably similar in appearance to globular reovirus factories formed in infected cells, as visualized by either phase-contrast or immunofluorescence (IF) microscopy (4,7,30), suggesting that NS forms the matrix of the factories (7).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, the stack images suggested that viroplasms are well-defined spherical structures. In reoviruses, it has also been reported that sNS, the non-structural protein homologous to rotavirus NSP2 with ssRNA binding activity and capacity to form higher-order homo-oligomeric structures (Huismans & Joklik, 1976;Richardson & Furuichi, 1985;Gillian & Nibert, 1998;Gillian et al, 2000), can also form inclusionbody-like structures when co-expressed with reovirus protein mNS (Becker et al, 2003). NS2 of bluetongue virus and rotavirus NSP2 have been considered to be proteins of similar function, since they share NTPase activity, non-specific ssRNA binding and localization to inclusions bodies Fillmore et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The capsid shells are built by virus protein-protein interaction and vital to impede host cell immune clearance mechanism. The Y2H system has been become a powerful genetic approach to identify protein-protein interaction in Reoviridae [4,7,30,34]. For application in GCRV protein-protein interaction identification, GCRV873 (GCRV genotype I) NS80 is verified to interact with proteins NS38, VP4, and VP6 as well as itself, whereas no interactions involving the four protein pairs NS38-VP4, NS38-VP6, VP4-VP4, and VP4-VP6 are observed [6].…”
Section: Discussionmentioning
confidence: 99%